Moderate Cardiovascular Risk Factor among Indonesian: Do Carotid Intima-media Thickness (CIMT) Predict Further? - Rina Mawarti; Denny Suwanto; Johanes Nugroho Eko Putranto; Djoko Soemantri (Universitas Airlangga, 2020)
Background. Determining management strategies in an individual with intermediate cardiovascular risk represent a great challenge. The impact of increased CIMT to improve estimated cardiovascular disease (CVD) risk score in individual at intermediate cardiovascular risk has not yet been fully elucidated. Aims. For this reason, we sought to determine the association between CIMT increment and incident of CVD. Methods. We conducted a longitudinal retrospective cohort study involving 28 patients with intermediate cardiovascular risk (Framingham risk score 10% - 20%). Subjects with criteria fulfillment had their data collected through history taking, physical examination, and CIMT re-measurement using echocardiography. Results. Bivariate analysis with regression logistic showed significant correlation between increased CIMT with CVD event (p= 0.016). CIMT measurement is a plausible noninvasive method to predict subclinical cardiovascular disease to further promote more aggressive management.